Narratives from the Sephardic Atlantic : Blood and Faith - Perelis, Ronnie (Book collections on Project MUSE., 2016)
Blood and Dreams looks at three autobiographical texts written by individuals caught within the matrix of inquisitorial persecution, expanding global trade and crypto-Jewish activity in the early modern period. Luis de Carvajal, el mozo (1567-1596), also known as Joseph Lumbroso moved from Spain to Mexico when he was a teenager in 1580 and began writing his spiritual autobiography after his first inquisitorial trial in 1589. The Portuguese merchant Antonio de Montezinos (1604-1647), recounts his life-changing encounter with the lost tribe of Reuben living in the northern Andes. His account dates to 1644 but was only published in 1650 as part of Menasseh ben Israel's treatise on the fate of the Lost Tribes, Mikveh Israel/ Esperanza de Israel. Manuel Cardoso de Macedo (1585-1652) was an Azorean Old Christian who first embraced Calvinism before leaving Christianity behind and converting to Judaism. He wrote his spiritual autobiography, La Vida del buenaventurado Abraham Pelengrino Guer while living as a Jew in Amsterdam at some point after the 1620's.